CYCLOSTRATIGRAPHY: A METHODOLOGICAL APPROACH (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
Aim of this study is a synthetic description of the most used methodologies of cylostratigraphic analysis for the astronomical calibration of sedimentary sequences. The different numerical solutions of the insolation curve and, in particular, the most used astronomic curve La90 (1,1) are analyzed. Then, a detailed description of the methodologies for the astronomic calibration of different sedimentary sequences i) on the basis of a litho-stratigraphic approach and ii) on the basis of a spectral analysis applied to faunal and geochemical climate-sensitive records, is proposed.